Uusi hopearahakätkö hellenistiseltä kaudelta? - Jani Oravisjärvi (Suomen Numismaattinen Yhdistys, 2025)
A new hoard from Hellenistic period?" is an an attempt to reconstruct of Athenian and other Hellenistic tetradrachms which was sold by a German coin dealer in 2013. There were at least 34 silver coins, all with a grey patina with a lilac tone. Because some of the coins of Antiochus VII can be posthumous, the hoard may date the 120s B. C. The hoard was probably found in Syria.